Guía para el cultivo del espárrago. - Federación Nacional de Cafeteros de Colombia, Bogotá (Colombia) (Federación Nacional de Cafeteros de Colombia - FEDECAFE, 1985)
Esparrago-Espárragos - Asparragus Officinalis L.